REKONSILIASI PARADIGMA PENDIDIKAN ISLAM TRADISIONAL DENGAN PERSPEKTIF BARU DALAM KONTEKS PENINGKATAN KOMPETENSI GURU - M. Yasir Arafat (UNISAN JURNAL, 2024)
This study aims to investigate the process of reconciling traditional Islamic education paradigms with new perspectives in the context of enhancing teacher competency. Combining qualitative and case study approaches, the research explores the challenges, strategies, and implications of such efforts. Data were collected through in-depth interviews, observations, and document analysis from several traditional Islamic educational institutions undergoing changes. Key findings highlight implementation challenges such as resource limitations and resistance to change, as well as strategies to address these challenges, including the development of balanced curricula and strengthening teacher training. The implications of these findings include the importance of developing policies and practices that support the reconciliation of traditional Islamic education paradigms with new perspectives to create a more adaptive and inclusive educational environment. This study contributes to understanding the complexity of this process and provides a basis for further research in the field of Islamic education.